2007
DOI: 10.1210/jc.2006-2147
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Phenotype Analysis in Five Patients with Isolated Hypogonadotropic Hypogonadism due to a L102P Inactivating Mutation of GPR54

Abstract: GPR54 inactivation does not impede neuroendocrine onset of puberty; rather, it delays and slows down pubertal maturation of the gonadotropic axis. The L102P loss of function mutation in GPR54 results in a more quantitative than qualitative defect of gonadotropic axis activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 40 publications
(46 reference statements)
9
126
2
6
Order By: Relevance
“…These mutations include six point mutations (p.L148S, p.R297L, p.C223R, p.R331X, p.X399R, and p.L102P) (3,5,14), one 155-bp deletion (4), and one insertion (c.1001_1002insC) (6). Taking into consideration the 312 patients with normosmic IHH reported to have been screened, including the 69 patients from this study, mutations reported in KISS1R gene are responsible for !5% of cases of normosmic IHH.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations include six point mutations (p.L148S, p.R297L, p.C223R, p.R331X, p.X399R, and p.L102P) (3,5,14), one 155-bp deletion (4), and one insertion (c.1001_1002insC) (6). Taking into consideration the 312 patients with normosmic IHH reported to have been screened, including the 69 patients from this study, mutations reported in KISS1R gene are responsible for !5% of cases of normosmic IHH.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Tenenbaum-Rakover et al (107) identified five patients with CHH belonging to two unrelated consanguineous Arab-Muslim families from Syria and Israel. All the affected subjects were homozygous for another GPR54/KISS1R missense mutation that replaced a leucine with a proline at residue 102 (L102P), and completely abolished GPR54 signaling.…”
Section: Chh In Patients Carrying Gpr54/kiss1r Mutationsmentioning
confidence: 99%
“…Análises de segregação familiar realizadas nessas famílias mostraram que os indiví-duos portadores de alterações no gene KISS1R em heterozigose apresentavam um desenvolvimento puberal normal, confirmando um modelo de herança autossô-mica recessiva para essa doença. Mutações no KISS1R são consideradas uma causa rara de HHI, com uma frequên cia inferior a 5% em casos esporádicos (1,6%), porém com uma frequência mais elevada entre os casos familiares (20,8%) (6,10,(63)(64)(65).…”
Section: Defeitos Na Síntese E Secreção De Gnrh Gene Kiss1runclassified
“…O fenótipo reprodutivo desses indivíduos varia de hipogonadismo parcial a completo. De modo geral, o perfil neuroendócrino desses pacientes revela baixa amplitude dos pulsos de LH, sugerindo uma secreção reduzida de GnRH (10,65). É notável que tanto homens quanto mulheres portadores de mutações no KISS1R apresentam resultados satisfatórios no tratamento, seja ele realizado com a administração exógena de gonadotrofinas ou com infusão de GnRH pulsátil a longo prazo (10,63,65,66).…”
Section: Defeitos Na Síntese E Secreção De Gnrh Gene Kiss1runclassified
See 1 more Smart Citation